Characterization of a new set of eight geochemical reference materials for XRF major and trace element analysis - Rufino Lozano; Juan Pablo Bernal (Revista Mexicana de Ciencias Geológicas)
Eight new geochemical reference materials for the analysis of major and trace elements in typical geological matrices have been prepared, and their physical and chemical homogeneity has been thoroughly assessed. The materials (IGL sample series) consist of a lateritic soil, a dolomite, a limestone, an andesite, three different syenites and a gabbro, all of them sampled at different localities from Mexico. The results indicate that the IGL samples are physically homogeneous down to a sub-batch of 0.2 g with a 0.05 significance level. Major and trace element provisional composition of these materials was obtained by wavelength-dispersive X-ray fluorescence spectrometry (WD-XRF). Statistical evaluation to verify for “sufficient homogeneity” was applied and sufficient chemical homogeneity at the 0.05 significance level was demonstrated. Calibration curves were constructed using the IGL samples in order to assess their performance as reference materials. Analyses of international reference materials (RGM-1, AGV-1, SDO- 1, and Es-3) demonstrate the reliability of the IGL samples for calibration and intercalibration purposes. Provisional concentrations for 24 major and trace elements, as well as FeO and loss on ignition (LOI) values, are provided for all IGL reference materials.